What shapes representation preferences: Teaching environment versus thinking types? - (:unkn) unknown (Oxford University Press, 2014)
Problem-solving behaviours of students have been comprehensively considered in much research. Students' differences in their thinking processes influence their mathematical processing. In this study, we focused on whether mathematical thinking types affect what representations they use for integrals. The participants of the study were 37 undergraduate studentswhowere enrolled for a calculus course and were selected through apurposeful sampling technique in case study design. Data collection techniques were test, observation and interview. Tests were used to identify learners' preferred representations according to their type of thinking. Participants' views on preferences for representations are evaluated by interviews. The data gained in the study were analysed and interpreted through a classification method and descriptive statistics. Results show that, although participants' mathematical thinking types have some effect on their representation preferences, the participants generally preferred algebraic representation. It seems that participants' problem-solving behaviours are more affected by teaching environment than by preferred thinking types. Other findings from the study are discussed based on the literature. © The Author 2014.Published by Oxford University Press on behalf of The Institute of Mathematics and its Applications. All rights reserved.